PENGARUH PENAMBAHAN SENYAWA NaCl PADA PEMBUATAN KARBON AKTIF DARI LIMBAH AMPAS TEBU (BAGASSE) TERHADAP AIR BUANGAN RUMAH TANGGA DENGAN PARAMETER pH DAN TSS - Ireng Sari, Melati; Riski, Tiara (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2024)
Bagasse waste is a residue from the sugarcane milling process so that it is used as activated carbon. The production of activated carbon is carried out in 3 stages, namely the dehydration process, the carbonization process, and the activation process. The addition of NaCl compounds was carried out with the aim of testing whether salt can be used as an activator or not, with NaCl concentrations of 5%, 10%, 15%. The carbonization process was carried out at 300oC for 30 minutes and the size obtained was 80 mesh. The parameters of activated carbon tested were moisture content and ash content. While the domestic water samples are pH, and TSS. The test results obtained were pH 7 and TSS 5 – 45 mg/L. This value does not indicate a decrease in raw wastewater content. So it can be concluded that salt compounds cannot be used as activators because they cannot open the pores in activated carbon.